Mengurai Makna Pelayanan Mukjizat Paulus Menurut Kisah Para Rasul 20:1-12 Dari Bingkai Kaum Pentakostal - Manurung, Kosma (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
The Apostle Paul is a very important theologian in the New Testament who has also set an example for believers in many generations in terms of faith, ministry, and daily life. This article intends to analyze the meaning of the apostle Paul's miraculous ministry in Acts 20:1-12 from the perspective of the Pentecostals. By using a qualitative descriptive method and supported by literature review, it is hoped that it will be able to explain in a careful, in-depth, and academically strong manner related to the Bible's account of the story of Paul's ministry, the description of Paul's ministry in Acts 20:1-12, as well as the meaning of the Pentecostals for the story in this passage. In conclusion, Pentecostals interpret the story of the apostle Paul's miraculous ministry as the importance of having an encounter with God, the importance of discipleship, perseverance in serving God, and the manifestation of God's power that accompanies the ministry of believers.AbstrakRasul Paulus adalah teolog yang sangat penting di Perjanjian Baru yang juga telah memberikan teladan bagi orang percaya di banyak generasi baik dalam hal iman, pelayanan, maupun keseharian hidup. Artikel ini bermaksud mengurai makna pelayanan mukjizat rasul Paulus di Kisah Para Rasul 20:1-12 dari bingkai kaum Pentakostal. Dengan mengunakan metode deskriptif kualitatif dan dukungan kajian literatur diharapkan mampu menjelaskan secara cermat, mendalam, serta kuat secara akademik terkait catatan Alkitab tentang kisah pelayanan Paulus, uraian pelayanan Paulus dalam Kisah Rasul 20:1-12, juga pemaknaan kaum Pentakostal atas kisah dalam perikop ini. Disimpulkan, kaum Pentakostal memaknai kisah pelayanan mukjizat rasul Paulus ini sebagai arti penting mengalami perjumpaan dengan Tuhan, pentingnya pemuridan, ketekunan dalam melayani Tuhan, serta adanya manifestasi kuasa Tuhan yang menyertai pelayanan orang percaya.